The influence of reference coal price and inflation on the share price of sharia coal companies (Case Study of PT. Adaro Energy Indonesia Tbk) - Sukron, Jaenudin; Wazin, Wazin; Peristiwo, Hadi (Institute of Accounting Research and Novation (IARN), 2024)
In the context of the coal industry, fluctuations in benchmark coal prices and inflation rates are important factors that correlate with the financial performance of coal sector companies and their stock values in the capital market. This research aims to investigate the correlation between benchmark coal prices and inflation with the Sharia stock price of PT Adaro Energy Indonesia Tbk (ADRO), using historical data from 2020 to 2023. Utilizing multiple linear regression analysis, this study shows that collectively, benchmark coal prices and inflation have a significant influence on ADRO's stock price. Individually, benchmark coal prices have an influence on ADRO's stock price, whereas inflation does not have an impact on ADRO's stock price.